2015 IEEE 56th Annual Symposium on Foundations of Computer Science 2015
DOI: 10.1109/focs.2015.17
|View full text |Cite
|
Sign up to set email alerts
|

Language Edit Distance and Maximum Likelihood Parsing of Stochastic Grammars: Faster Algorithms and Connection to Fundamental Graph Problems

Abstract: Given a context free language L(G) over alphabet Σ and a string s ∈ Σ * , the language edit distance problem seeks the minimum number of edits (insertions, deletions and substitutions) required to convert s into a valid member of L(G). The well-known dynamic programming algorithm solves this problem in O(n 3 ) time (ignoring grammar size) where n is the string length [Aho, Peterson 1972, Myers 1985. Despite its numerous applications, to date there exists no algorithm that computes exact or approximate language… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…This leads to an exact algorithm that runs in 2 O(d) · n time. In another work, Saha [11] gave an algorithm for computing a (1 + )-approximation to distance to a fixed context-free grammar. The running time of the algorithm is O(n ω / O(1) ).…”
Section: Previous Results and Related Workmentioning
confidence: 99%
“…This leads to an exact algorithm that runs in 2 O(d) · n time. In another work, Saha [11] gave an algorithm for computing a (1 + )-approximation to distance to a fixed context-free grammar. The running time of the algorithm is O(n ω / O(1) ).…”
Section: Previous Results and Related Workmentioning
confidence: 99%
“…It is conjectured to require n 3−o(1) time, and many problems, especially on graphs, are known to be equivalent to or at least as hard as APSP, see e.g. [48, 60,6,3,49,8,27]. 3 The 3-SUM problem is to decide if a given set of n integers contains three that sum to zero.…”
mentioning
confidence: 99%
“…Due to known conditional lower bound results for parsing [30,1], LED cannot be approximated within any multiplicative factor in time o(n ω ) (unless cliques can be found faster). Interestingly, if we only ask for insertions as edit operations, Sahe also showed that a truly sub-cubic exact algorithm is unlikely due to a reduction from APSP [41,48]. In contrast, here we show that with insertions and deletions (and possibly substitutions) as edit operations, LED is solvable in truly sub-cubic time.…”
Section: Related Workmentioning
confidence: 63%
“…It is relatively easy to adapt Valiant's parser to this scored parsing problem, the main difference being that Boolean matrix multiplications are replaced by (min, +)-products. It follows that scored parsing can be solved up to logarithmic factors in the time needed to perform one (min, +)-product (see also [41]). In particular, applying Williams' algorithm for the (min, +)-product [51], one can solve scored parsing in O(n 3 /2 Θ( √ log n) ) time, which is the current best running time for this problem.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation